The influence of low-intensity ultrasound on the properties of cell cultures - Jiří ADLER; Ivo HRAZDIRA; Jitka HANZLOVÁ; Vera ZAJÍCOVÁ (Archives of Acoustics)
In the present paper bovine kidney cell cultures were used as an experimental model for the study of the biophysical mechanism of ultrasonic action. In the first series of experiments functional and morphological changes in the cells immediately after sonication were evaluated. A decrease in viability and degenerative morphological changes in the cells were found. In the second series the sonicated cells were seeded in Roux bottles and grown in the optimal conditions. The growth properties of the cells were evaluated at different time intervals after sonication. Significant stimulation of the cell growth was demonstrated after the action of ultrasound intensity of 1.0 kWm^{-2}. However, after the action of ultrasound intensities above 3.0 kWm^{-2} the inhibition of the cell growth was found.